SUJETO Y OBJETO DE LA VERBARIZACIÓN Y SU RELACIÓN CON EL ACTANTE EN LINGÜÍSTICA RUSA - Lazarev ,; Smirnova ,; Lakhaeva , (Revista Inclusiones, 2018)
The article discusses the categories of "subject", "object" and "actant". It is proved that in modern linguistics such a distinction of concepts is necessary, since it allows you to avoid new disputes about their essence and the best ways of differentiation. The article proposes to significantly limit the use of the concepts "subject" and "object", and instead use the term "actant" in the broad sense of the word, meaning not only living beings, but also inanimate objects and concepts.